Magnetism in Mn-doped ZnO nanoparticles prepared by a co-precipitation method - Jayakumar, O D; Salunke, H G; Kadam, R M; Mohapatra, Manoj; Yaswant, G; Kulshreshtha, S K (Nanotechnology, 2006)
We report the synthesis of nominal 2 and 5 at.% Mn-doped ZnO nanocrystalline particles by a co-precipitation method. Rietveld refinement of x-ray diffraction data revealed that Mn-doped ZnO crystallizes in the monophasic wurtzite structure and the unit cell volume increases with increasing Mn concentration. DC magnetization measurements showed ferromagnetic ordering above room temperature with HH 150 Oe for nominal 2 at.% Mn-doped ZnO nanoparticles annealed at 675 K. A distinct ferromagnetic resonance (FMR) signal was observed in the EPR spectra of the 2 at.% Mn-doped ZnO nanoparticles annealed at 675 K. EPR measurements were used to estimate the number of spins participating in ferromagnetic ordering. Of the total Mn present in the 2 at.% Mn ZnO lattice, 25% of the Mn2+ ions were responsible for ferromagnetic ordering, whereas nearly 5% of the Mn2+ ions remained uncoupled (isolated spins). A well resolved EPR spectrum of 5% Mn-doped ZnO samples annealed at 875-1275 K (g = 2.007, A = 80 G, D = 210 G and E = 15 G) confirmed that Mn was substitutionally incorporated into the ZnO lattice as Mn2+. On increasing the temperature of annealing beyond 1075 K an impurity phase emerges in both the 2 and 5 at.% Mn-doped ZnO samples, which has been identified as a variant of (Znl_xMn(II)X)Mn(III)204 with Tc ' 15 K. Our results indicate that the observed room temperature ferromagnetism in Mn-doped ZnO can be attributed to the substitutional incorporation of Mn at Zn-sites rather than due to the formation of any metastable secondary phases.